A Novel Staining Method for Detection of Brain Perivascular Injuries Induced by Nanoparticle: Periodic Acid-Schiff and Immunohistochemical Double-Staining - Onoda, Atsuto; Hagiwara, Shin; Kubota, Natsuko; Yanagita, Shinya; Takeda, Ken; Umezawa, Masakazu (Frontiers in Toxicology, 2022)
Background: To protect developing brain from any unfavorable effects, it is necessary to construct experimental techniques that can sensitively detect and evaluate developmental toxicity. We have previously shown that brain perivascular tissues, especially perivascular macrophages (PVMs), respond sensitively even to weak stimuli by foreign toxicants such as low-dose exposure to nanoparticle. This paper shows the protocol of a novel staining method that enables easy detection and rapid evaluation of brain perivascular abnormalities. Methods: As weak stimulus, low-dose of carbon black nanoparticle (95 μg/kg) or titanium dioxide nanoparticle (100 μg/kg) was intranasally administered to pregnant mice at gestational days 5 and 9. The offspring brains were used to confirm the properties of PVMs and to find suitable protocols for the detection and evaluation of the mild denaturation of PVMs. Furthermore, various procedures of novel combinational double staining including periodic acid-Schiff (PAS) staining and immunohistochemistry were examined. In addition, we checked the alterations in neurotransmitter levels and the behaviors of the offspring. Results and discussion: Maternal exposure to low-dose of nanoparticle at levels where no significant effects on the brain were observed, such as abnormal behavior, alteration of neurotransmitter levels, or microglial activation, resulted in mild denaturation of the PVMs, which was captured by PAS staining. However, it was difficult to detect and determine slight histopathological alterations. Therefore, we established PAS-immunohistochemical double-staining method for the brain. This double staining method enabled easy detection and rapid evaluation of brain perivascular abnormalities and the relationship between PVMs and the surrounding cells. In addition, this double staining allows evaluation of the histopathological denaturation of the PVMs and the associated abnormalities in the surrounding tissues in the same section. Conclusions: The slight responses of brain perivascular tissues, such as mild denaturation of PVMs, were sensitively and easily determined by the PAS-immunohistochemical double-staining method. This double staining method is a powerful tool to assess brain perivascular injuries including PVM denaturation and the relationship between the expression of various molecules and the morphology of PVMs. We propose that the observation of the tissue around brain blood vessels using the double staining provides potential endpoints to evaluate developmental neurotoxicity.